If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + -3) + -1 = 2 Reorder the terms: (-3 + 4x) + -1 = 2 Remove parenthesis around (-3 + 4x) -3 + 4x + -1 = 2 Reorder the terms: -3 + -1 + 4x = 2 Combine like terms: -3 + -1 = -4 -4 + 4x = 2 Solving -4 + 4x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 4x = 2 + 4 Combine like terms: -4 + 4 = 0 0 + 4x = 2 + 4 4x = 2 + 4 Combine like terms: 2 + 4 = 6 4x = 6 Divide each side by '4'. x = 1.5 Simplifying x = 1.5
| -3(-5+x)=15 | | 5.3x+25.35=1.2(7.8+7.7x)+2.2 | | 4(u+1)=12 | | x+12=9x-4 | | -4=5x-7 | | 2.8(6.23m+6.2)+2.8m=1.9+15.5256 | | x+2=9x-4 | | 81=-3 | | -41z-98=z-(-31) | | v+7.7+3.8v-5.4866=1.244v+4.083v | | 11c-10c-1=16 | | 9x-2-8x-13=15 | | 4(-3+r)=-36 | | 6x+13-x=14-7x+9x | | 1/2x5/8 | | -41(z-98)=z-(-31) | | 3x+14=9x+8 | | 6x+7x-80=100-7x | | -5b=65 | | -6.3(1-0.2n)+1.4n=-6.7(1.6-4n) | | 4x^2+8y=0 | | y/7-3=21 | | -2(a+14)+a=4(a+8) | | 5x^2-22x+10=0 | | 3r+6+2r=-9 | | 6(k-2)+2(k-53)=2 | | -4(r+17)=-8 | | 3/7=6/k-9 | | 1/4=(-3/4)t | | 3-8=y-9 | | -6.6(x-7.6)-1.43=-3.3(1-5.8x) | | 1120+x/3+x/5=x |